Species of Neoperla (Plecoptera: Perlidae) from Hubei, China - Li, Weihai; Wang, Guoquan; Lu, Wenyan (Zootaxa, 2012)
The perline genus Neoperla is reported from Hubei Province, China for the first time. We describe and illustrate two spe-cies with color photographs, Neoperla hubeiensis sp. nov., and N. cavalerieri (Navás). The new species is compared to similar taxa.